Love and other consolation prizes [compact disc, unabridged] : a novel - Ford, Jamie (Random House Audio ; Books on Tape, 2017)
A powerful novel, inspired by a true story, about a boy whose life is transformed at Seattle's epic 1909 World's Fair.